PROFESIONALISME GURU DALAM MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA - MA, Dr. Yusutria (Kopertis Wilayah X (Sumbar, Riau, Jambi, dan Riau Kepulauan), 2017)
Abstract The quality of human resources (SDM), among others, determined by the quality and level of education. The quality of education is low causing low quality of human resources; the higher the education level, the higher the quality of human resources that will affect the way of thinking, reasoning, insight, breadth and depth of knowledge. The professionalism of teachers in improving the quality of human resources will be reflected in the implementation of the tasks that are marked with expertise both in material and methods. With his expertise, a teacher is able to demonstrate its independence, both personal as well as professional stakeholders. In addition to their expertise, professional figure teacher demonstrated through its responsibility in implementing all professional dedication should be able to assume and carry out the responsibility as a teacher to the students, parents, community, nation state, and religion. Teacher professional social responsibility, intellectual, moral, and spiritual. Keywords: professionalism, improve human resources. Abstrak Kualitas sumber daya manusia (SDM) antara lain ditentukan oleh mutu dan tingkat pendidikan. Kualitas pendidikan yang rendah menyebabkan kualitas SDM rendah; makin tinggi tingkat pendidikan maka makin tinggi pula kualitas SDM yang akan berpengaruh terhadap cara pikir, nalar, wawasan, keluasan dan kedalaman pengetahuan. Profesionalisme guru dalam meningkatkan kualitas SDM akan tercermin pada pelaksanaan tugas-tugas yang ditandai dengan keahlian baik dalam materi maupun metode. Dengan keahliannya itu, seorang guru mampu menunjukkan otonominya, baik pribadi maupun sebagai pemangku profesinya. Di samping dengan keahliannya, sosok profesional guru ditunjukkan melalui tanggung jawabnya dalam melaksanakan seluruh pengabdiannya profesional hendaknya mampu memikul dan melaksanakan tanggung jawab sebagai guru kepada peserta didik, orang tua, masyarakat, bangsa negara, dan agamanya. Guru professional mempunyai tanggung jawab sosial, intelektual, moral, dan spiritual. Kata kunci: profesionalisme, meningkatkan, sumber daya manusia.